2021
DOI: 10.1002/acp.3843
|View full text |Cite
|
Sign up to set email alerts
|

Testing the affective events theory: The mediating role of affect and the moderating role of mindfulness

Abstract: This study aims to expand the knowledge on the affective events theory by:(1) testing the mediating role of affect in the relationship between micro-daily events and well-being, (2) and analyzing the moderating role of mindfulness in this mediated relationship. To achieve these goals, we collected data with 393 working adults. The results showed that: (1) affect mediates the relationship between micro-daily events and well-being; (2) mindfulness moderates the mediated relationship between micro-daily events an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…Second, we only focused on daily negative affect, which left out other possibilities, such as the positive ones. While our concern in negative affect is justified by the existence of fewer studies exploring it, we recognize that positive affect is relevant for daily mental health ( Junça-Silva et al, 2021 ). Third, the measures of uncertainty and neuroticism presented moderate reliability indices which might be due to using few items to assess it.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we only focused on daily negative affect, which left out other possibilities, such as the positive ones. While our concern in negative affect is justified by the existence of fewer studies exploring it, we recognize that positive affect is relevant for daily mental health ( Junça-Silva et al, 2021 ). Third, the measures of uncertainty and neuroticism presented moderate reliability indices which might be due to using few items to assess it.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, future studies could consider exploring the differences of each kind of animal for practical purposes, e.g., performance. Fourth, future research could analyze the situational conditions by which pet-friendly practices predict OI and well-being, for instance through micro-daily events at work [65]. Fifth, future studies should explore the role of different pet species, e.g., dogs, or cats, because there are studies that demonstrated that different species had different effects.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…AET is not only used to explain work-related emotions, but also has expanded to many areas of research in recent years, such as affect mediating the relationship between micro-daily events and well-being, 28 job satisfaction and job insecurity mediating the relationship between incivility and intrapreneurial behavior. 29 Hence, AET has become a significant theory in the field of organizational behavior and HRM, the motivation of researchers increased to test how employees’ behavior is affected by various events and emotions.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%